The Effect of Lower-Body Positive Pressure on the Cardiorespiratory Response at Rest and during Submaximal Running Exercise - Stucky, Frédéric; Vesin, Jean-Marc; Kayser, Bengt; Uva, Barbara (Frontiers in Physiology, 2018)
Anti-gravity treadmills facilitate locomotion by lower-body positive pressure (LBPP). Effects on cardiorespiratory regulation are unknown. Healthy men (30±8 y, 178.3±5.7 cm, 70.3±8.0 kg; mean±SD) stood upright (n=10) or ran (n=9) at 9, 11, 13 and 15 km.h-1 (5 min stages) with LBPP (0, 15, 40 mmHg). Cardiac output (CO), stroke volume (SV), heart rate (HR), blood pressure (BP), peripheral resistance (PR) and oxygen uptake (VO2) were monitored continuously. During standing, LBPP increased SV (by +29±13 (+41%) and +42±15 (+60%) ml, at 15 and 40 mmHg, respectively (p<0.05)) and decreased HR (by -15±6 (-20%) and -22±9 (-29%) bpm (p<0.05)) resulting in a transitory increase in CO (by +1.6±1.0 (+32%) and +2.0±1.0 (+39%) l.min-1 (p<0.05)) within the first seconds of LBPP. This was accompanied by a transitory decrease in end-tidal PO2 (by -5±3 (-5%) and -10±4 (-10%) mmHg (p<0.05)) and increase in VO2 (by +66±53 (+26%) and +116±64 (+46%) ml.min-1 (p<0.05)), suggesting increased venous return and pulmonary blood flow. The application of LBPP increased baroreflex sensitivity (BRS) (by +1.8±1.6 (+18%) and +4.6±3.7 (+47%) at 15 and 40 mmHg LBPP, respectively P<0.05). After reaching steady-state exercise CO vs VO2 relationships remained linear with similar slope and intercept for each participant (mean R2 = 0.84±0.13) while MAP remained unchanged. It follows that (1) LBPP affects cardiorespiratory integration at the onset of exercise; (2) at a given LBPP, once reaching steady-state exercise, the cardiorespiratory load is reduced proportionally to the lower metabolic demand resulting from the body weight support; (3) the balance between cardiovascular response, oxygen delivery to the exercising muscles and blood pressure regulation is maintained at exercise steady-state; and (4) changes in baroreflex sensitivity may be involved in the regulation of cardiovascular parameters during LBPP.